A 128-channel receive-only cardiac coil for highly accelerated cardiac MRI at 3 Tesla - Schmitt, Melanie; Potthast, Andreas; Sosnovik, David E.; Polimeni, Jonathan R.; Wiggins, Graham C.; Triantafyllou, Christina; Wald, Lawrence L. (Magnetic resonance in medicine, 2008)
A 128‐channel receive‐only array coil is described and tested for cardiac imaging at 3T. The coil is closely contoured to the body with a “clam‐shell” geometry with 68 posterior and 60 anterior elements, each 75 mm in diameter, and arranged in a continuous overlapped array of hexagonal symmetry to minimize nearest neighbor coupling. Signal‐to‐noise ratio (SNR) and noise amplification for parallel imaging (G‐factor) were evaluated in phantom and volunteer experiments. These results were compared to those of commercially available 24‐channel and 32‐channel coils in routine use for cardiac imaging. The in vivo measurements with the 128‐channel coil resulted in SNR gains compared to the 24‐channel coil (up to 2.2‐fold in the apex). The 128‐ and 32‐channel coils showed similar SNR in the heart, likely dominated by the similar element diameters of these coils. The maximum G‐factor values were up to seven times better for a seven‐fold acceleration factor (R = 7) compared to the 24‐channel coil and up to two‐fold improved compared to the 32‐channel coil. The ability of the 128‐channel coil to facilitate highly accelerated cardiac imaging was demonstrated in four volunteers using acceleration factors up to seven‐fold (R = 7) in a single spatial dimension. Magn Reson Med 59:1431–1439, 2008. © 2008 Wiley‐Liss, Inc.